2018
DOI: 10.1186/s12889-018-5512-8
|View full text |Cite
|
Sign up to set email alerts
|

Suicide prevention gatekeeper training in the Netherlands improves gatekeepers’ knowledge of suicide prevention and their confidence to discuss suicidality, an observational study

Abstract: BackgroundThe gatekeeper training is designed to help identify suicidal individuals, respond to suicidal ideation and refer to help. The internationally widely used training shows promising results. This is the first study presenting its effectiveness in the Netherlands and the first study investigating the effect in different employment sectors.MethodsIn an observational study, 113 Suicide Prevention – the Dutch suicide prevention expertise centre and lifeline - trained 526 professionals as gatekeepers. Chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 44 publications
0
39
0
5
Order By: Relevance
“…An overwhelming 95% of respondents identified the need for continuing education in this area. Evidence indicates both in-person and online training programs can be effective at increasing suicide-related awareness, knowledge, and confidence among workers from a wide variety of professions (Ghoncheh et al, 2016; Terpstra et al, 2018). Training may help clarify the role of OT practitioners in youth suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An overwhelming 95% of respondents identified the need for continuing education in this area. Evidence indicates both in-person and online training programs can be effective at increasing suicide-related awareness, knowledge, and confidence among workers from a wide variety of professions (Ghoncheh et al, 2016; Terpstra et al, 2018). Training may help clarify the role of OT practitioners in youth suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies examining the role of professionals in suicide prevention have included a range of disciplines such as physicians, nurses, social workers, psychologists, and educators (e.g., Silva et al, 2016; Terpstra et al, 2018; Zuckerbrot et al, 2018). To the best of our knowledge, no studies to date have examined OT practitioner preparation related to suicide in general, nor specifically related to youth suicide.…”
mentioning
confidence: 99%
“…Firstly, community gate keepers are trained to identify suicide risk, to make contact and ‘open the gates’ for help-seeking [ 17 ]. A recent observational study demonstrated significant improvements in gatekeepers’ knowledge of suicide prevention and their confidence to discuss suicidality after gatekeeper training [ 35 ]. Gatekeeper training could therefore make gatekeepers aware of risk-groups for non-disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge will be assessed using a self-report gatekeeper training questionnaire derived from previously validated questionnaires in gatekeeper training surveys [35], with one item adapted to Indian settings. The questionnaire consists of eight questions gauging knowledge about suicides and suicidal behaviour; talking to someone who is suicidal and arranging help; and ability to manage clients with a high risk of suicide in a timely and appropriate manner.…”
Section: Intervention 3: Primary Outcomementioning
confidence: 99%